2010
DOI: 10.3732/ajb.0900341
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and ecophysiological significance of sugar utilization by the peat moss Sphagnum compactum (Sphagnaceae) and the common charophycean associates Cylindrocystis brebissonii and Mougeotia sp. (Zygnemataceae)

Abstract: Our results indicate that plant mixotrophy is an early-evolved trait. The results also indicate that quantitative differences in sugar utilization by bryophytes and charophycean algae correlate with relative investments in protective cell-wall polyphenolics measured in previous studies, suggesting that sugar utilization may subsidize the cost of producing phenolic wall compounds in bryophytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 46 publications
3
18
0
Order By: Relevance
“…Previous experiments with the same isolates of Sphagnum compactum, Marchantia polymorpha and Coleochaete that had been cultivated similarly revealed the occurrence of carbon limitation relieved by exogenous organic carbon. [37][38][39] In the present study, any such carbon limitation would have affected all experimental materials equally. To facilitate careful evaluation of results, investigations of the 5 selected taxa were conducted serially, with care taken to ensure that temperature and irradiance levels were the same during each experiment conducted with near-saturating levels of photosynthetically active radiation (PAR).…”
Section: Methodsmentioning
confidence: 84%
“…Previous experiments with the same isolates of Sphagnum compactum, Marchantia polymorpha and Coleochaete that had been cultivated similarly revealed the occurrence of carbon limitation relieved by exogenous organic carbon. [37][38][39] In the present study, any such carbon limitation would have affected all experimental materials equally. To facilitate careful evaluation of results, investigations of the 5 selected taxa were conducted serially, with care taken to ensure that temperature and irradiance levels were the same during each experiment conducted with near-saturating levels of photosynthetically active radiation (PAR).…”
Section: Methodsmentioning
confidence: 84%
“…To avoid microbial contamination but also allow gas exchange to occur, experimental dishes containing S. compactum were sealed at their overlapping edges with a single layer strip of Parafilm M, which is permeable to carbon dioxide at 1200 cc m 22 d 21 and oxygen at 150 cc m 22 d 21 at 237C and 0% RH and water vapor at 1 g m 22 at 387C and 90% RH (SPI Supplies). Previous experiments have demonstrated that S. compactum cultures grown in dishes closed with a Parafilm strip and without organic C additions are limited by inorganic carbon supply (Graham et al 2010). Even so, carbon dioxide levels were likely the same in all experimental dishes, and experimental comparisons were made only between cultures grown in the same type of dishes.…”
Section: Culture Provenance and Growth Mediummentioning
confidence: 99%
“…Biomass was determined using a Sartorius analytical weight type 1872 (Brinkman Instruments, Westbury, NY) and then utilized for quantitative acetolysis (Graham et al 2004(Graham et al , 2010 to determine the relative amount of hydrolysis-resistant biomass. Plants from three replicate culture dishes per treatment were dried and weighed, and cellulose was extracted and quantified.…”
Section: Harvesting and Biomass Assessmentmentioning
confidence: 99%
See 2 more Smart Citations